2020
DOI: 10.3390/ijerph17176227
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomy of Patients with Deficit Schizophrenia: An Exploratory Quantitative Meta-Analysis of Structural Neuroimaging Studies

Abstract: Little is known regarding the neuroanatomical correlates of patients with deficit schizophrenia or persistent negative symptoms. In this meta-analysis, we aimed to determine whether patients with deficit schizophrenia have characteristic brain abnormalities. We searched PubMed, CINAHL and Ovid to identify studies that examined the various regions of interest amongst patients with deficit schizophrenia, patients with non-deficit schizophrenia and healthy controls. A total of 24 studies met our inclusion criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(8 citation statements)
references
References 49 publications
(123 reference statements)
0
7
0
1
Order By: Relevance
“…Thus, Zhang et al [ 40 ] found a decrease in the gray matter volume in the cerebellum, the left inferior orbitofrontal cortex, and the right thalamus in schizophrenic patients with negative symptoms. Another work [ 41 ] described structural abnormalities (revealed by MRI) in the brain of schizophrenic patients with a neurocognitive deficit: the authors showed a decrease in the volume of the gray and white matter of the brain in this form of schizophrenia. A review by Kaladjian et al [ 42 ] mentioned a decrease in the gray matter density or a decrease in the cortical thickness in the frontal and temporal regions associated with negative symptoms and localized, in particular, in the medial frontal and orbitofrontal cortex, as well as in the area of the amygdala-hippocampal complex.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Zhang et al [ 40 ] found a decrease in the gray matter volume in the cerebellum, the left inferior orbitofrontal cortex, and the right thalamus in schizophrenic patients with negative symptoms. Another work [ 41 ] described structural abnormalities (revealed by MRI) in the brain of schizophrenic patients with a neurocognitive deficit: the authors showed a decrease in the volume of the gray and white matter of the brain in this form of schizophrenia. A review by Kaladjian et al [ 42 ] mentioned a decrease in the gray matter density or a decrease in the cortical thickness in the frontal and temporal regions associated with negative symptoms and localized, in particular, in the medial frontal and orbitofrontal cortex, as well as in the area of the amygdala-hippocampal complex.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of white matter changes in DS are inconclusive. The meta-analysis of Chee et al reports that there are differences in the WM and GM of individuals with DS compared to healthy controls (HC) [ 44 ]. However, this meta-analysis did not find any difference in WM and GM between DS and nondeficit syndrome (NDS) patients.…”
Section: Introductionmentioning
confidence: 99%
“…Right HG generally develops 1–2 weeks earlier than left HG during mid-to-late gestation ( 18 ) and is more complex ( 18 , 29 ); therefore, gyral formation of HG in D-Sz may be more affected on the right hemisphere. Since a meta-analysis of gray and white matter volumes across various brain regions found no significant differences between D- and ND-Sz ( 36 ) and these volumetric data are affected by various confounding factors (e.g., illness chronicity and medication), a better predictive biomarker of the clinical subtype and course of schizophrenia may be gross brain morphology, which is strongly related to early neurodevelopment.…”
Section: Discussionmentioning
confidence: 99%